Simultaneous Estimation of Chlorophyll a and Lipid Contents in Microalgae by Three-Color Analysis - Su, C.H.; Fu, C.C.; Chang, Y.C.; Nair, G.R.; Ye, J.L.; Chu, I.M.; Wu, W.T.
A method of rapid determination of chlorophyll a and lipid contents of microalgae based on colorimetric analysis of the digital images of the microalgae is proposed. The color variation of microalgae during cultivation is evaluated by the brightness of the three primary colors (red, green, and blue). The brightness values of the three primary colors are modeled as two linear correlation functions (RGB model)for microalgal chlorophyll a and lipid contents, respectively. The chlorophyll a and lipid contents predicted by the proposed model are compared with that determined by the standard methods. The good agreement of the model predictions with experimental results is demonstrated with a squared correlation coefficient (R2)of 0.99 for chlorophyll a and lipid. The reliability of the RGB model was verified in real cultivations of the microalgae in a photobioreactor. Growth dynamics, contents of chlorophyll a and lipid corresponded very well with previously reported studies.
Keywords: MICROALGAE; IMAGE ANALYSIS; CHLOROPHYLL; LIPID; RGB MODEL